Study of Knowledge, Attitude, Anxiety and Perception of Mental Health Service Needs Related to the COVID-19 Pandemic in Banyumas Regency, Central Java, Indonesia: A Cross-sectional Study - Yudhi Wibowo; Joko Mulyanto; VM Wahyu Siswandari; Siti Munfiah (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: In Banyumas, as of 27 June 2021, there were 15,809 confirmed cases and 669 deaths. Social restrictions with forced quarantine to fight the spread of diseases that have psychosocial impacts such as acute panic, anxiety, obsessive behavior, buildup, paranoia, depression and post-traumatic stress disorder. Community knowledge and attitudes affect compliance with the prevention and control of COVID-19. This study aimed to examine Knowledge, Attitudes, Anxiety & Perception of Mental Health Service Needs during the Covid-19 Pandemic.Subjects and Method: This was a cross-sectional study, conducted in Banyumas, Central Java, from July to August 2021. A total of 687 subjects was selected by snowball sampling. The dependent variable was anxiety. The independent variables were demographic data (initials, age, gender, home location, occupation, education level), marital status, pregnancy status, history of COVID-19, knowledge, attitudes, and perceptions of mental health service needs. The data were collected by questionnaire and analyzed using a multiple logistic regression. Results: The anxiety level increased wit age >60 years (OR= 0.60; 95% CI= 0.29 to 1.27; p= 0.001), not working (OR= 0.65; 95% CI= 0.29 to 1.46; p= 0.004), low level of education (OR= 2.07; 95% CI= 0.88 to 4.84; p=0.021), unmarried status (OR= 2.51; 95% CI= 1.67 to 3.78; p<0.001), COVID-19 survivors (OR= 1.96; 95% CI= 1.27 to 3.02; p= 0.003).Conclusion: Age, occupation, education level, unmarried status, COVID-19 survivors had a correlation with anxiety level. Keywords: knowledge, attitudes, anxiety, mental health service needs, COVID-19Correspondence: Yudhi Wibowo. Department of Public Health and Community Medicine, Medical Faculty, Jenderal Soedirman University. Jl. Dr. Gumbreg No.1, Mersi, Purwokerto, Banyumas, Central Java, Indonesia. Email: yudhi.wibowo@unsoed.ac.id. Mobile: +628112621904Journal of Health Promotion and Behavior (2022), 07(02): 142-151DOI: https://doi.org/10.26911/thejhpb.2021.07.02.06